KEARIFAN LOKAL : SISTEM PENGETAHUAN YANG DIGUNAKAN ORANG BADUY YANG ADA DI LEBAK BANTEN - Yusri; Sapriya; Encep Supriatna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The Baduy people, an indigenous community in Lebak, Banten, Indonesia, preserve a unique traditional knowledge system rooted in their cultural and spiritual beliefs. This article examines their knowledge systems across agriculture, environmental management, health, and social norms. The Baduy's practices emphasize harmony with nature and sustainable living, as reflected in their farming techniques, forest conservation efforts, and use of traditional medicine. Drawing on expert insights and field studies, this study highlights the resilience and relevance of Baduy knowledge in modern times, offering lessons for sustainable development and cultural preservation. The Baduy people, an indigenous group residing in the Lebak region of Banten, Indonesia, embody a unique cultural identity characterized by their adherence to traditional values and practices. This article aims to explore the knowledge system employed by the Baduy, highlighting its historical context, cultural significance, and the indigenous wisdom that has been passed down through generations. Drawing from various scholarly resources, this study examines the Baduy's relationship with nature, their social structures, and the spiritual beliefs that shape their worldview. Understanding the knowledge system of the Baduy not only enriches the study of anthropology but also promotes the discourse on cultural preservation in the face of modernity.